BUDAYA TOLERANSI DAN PERDAMAIAN DI MA’HAD AL-ZAYTUN DALAM KERANGKA SOLIDARITAS GLOBAL - Kholil Al Munawar; Anisa Fitri; Amalia Al-Tin Nurfalah; Saifudin (STKIP Subang, 2026)
The rise of intolerance in global society shows that diversity has not been fully managed as a source of social cohesion, but is often perceived as a threat to identity. This study aims to analyze the practices of tolerance and peace at Ma'had Al-Zaytun and their implications for the formation of global solidarity. The research uses a qualitative approach with a literature study method through the analysis of scientific literature on tolerance, peace, global solidarity, and multicultural education. The results of the study show that tolerance and peace at Ma'had Al-Zaytun do not stop at normative values, but are operationalized through religious moderation, cross-identity dialogue, transformational leadership, and the habit of living together in diversity. These practices shape the ethical orientation of students, connecting religious identity with universal human consciousness. The findings confirm that global solidarity is not an abstract construct, but rather an extension of social solidarity built through institutionalized local experiences of tolerance. The scientific contribution of this research lies in mapping the pedagogical mechanisms that connect the practice of tolerance with global solidarity as a sociocultural process. This research recommends the development of an experience-based tolerance education model as a strategy for strengthening social cohesion and preventing identity exclusivism in pluralistic societies.